Formation Constants of the Chelates of 2-Hydroxybenzilidine- o-Aminobenzothiazole with Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) Ions - DESAI, PULKESHI; AGARWAL, BALKRISHNA; PARAMESWARAN, PRIYA; LINGAM, BALASUBRAMANIAM; MANGAONKAR, KIRAN (Asian Journal of Chemistry, 2010)
Proton dissociation constant of the ligand and the stability constants of the complexes of Co(II), Ni(II), Cu(Il), Zn(Il) and Cd(Il) with 2-hydroxy-benzilidine-o-aminobenzothiazole have been determined potentiometrically at 30 ± 0.1 °C and at ionic strength 0.1 M in 75: 25 (V/V) dioxane-water medium. log K1 and log K2 values have been determined. The stabilities of the chelates follow the order Cu > Cd > Co > Ni > Zn.